2013
DOI: 10.1080/19361610.2013.765339
|View full text |Cite
|
Sign up to set email alerts
|

Developing Crisis Management Protocols in the Context of School Safety

Abstract: Creating a safe and secure environment for students is the responsibility of school administrators, therefore, developing a comprehensive threat and emergency preparedness plan is an essential component of fulfilling that duty. This article examines the factors influencing the development and implementation of effective emergency planning and practices in a large school district. The results of a survey of a large Midwestern K-12 school district are discussed within the context of providing a safe school envir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 12 publications
2
8
0
Order By: Relevance
“…The study identified administrative strategies for crime management as the use of closed circuit camera, electronic checking in of persons into the institutions, elimination of dark spots or hide out for criminals, character education, regular monitoring of activities, use of metallic crime detectors, collaboration with stakeholders, mounting of crime indicators at strategic points, community policing, organizing orientation on crime to newly admitted students, use of prayer and anti-crime cadets, demotion and sacking of staff fund guilty of criminal case. The finding is in concordance with Kingshott, and Mckenzie, (2013). They identified community support and assistance from law enforcement agents as strategies for ensuring safety and security in schools.…”
Section: Discussionsupporting
confidence: 79%
“…The study identified administrative strategies for crime management as the use of closed circuit camera, electronic checking in of persons into the institutions, elimination of dark spots or hide out for criminals, character education, regular monitoring of activities, use of metallic crime detectors, collaboration with stakeholders, mounting of crime indicators at strategic points, community policing, organizing orientation on crime to newly admitted students, use of prayer and anti-crime cadets, demotion and sacking of staff fund guilty of criminal case. The finding is in concordance with Kingshott, and Mckenzie, (2013). They identified community support and assistance from law enforcement agents as strategies for ensuring safety and security in schools.…”
Section: Discussionsupporting
confidence: 79%
“…For example, in a recent assimilation of school safety data, Dunlap (2013) focuses particularly on school violence as the central aspect of school safety. Literature often takes school violence as the contextual basis for school safety research and aims to develop response mechanisms to crises (e.g., Kingshott & McKenzie, 2013). The school violence literature primarily focuses on schools in the United States, where the effects of recent school shootings have prompted national discussion regarding the safety of schools and wider social issues, including gun laws (e.g., Jones, Waite, & Clements, 2012).…”
Section: School Safetymentioning
confidence: 99%
“…14 In the face of emergencies, the teachers' role has been defined as that of first responder. 15 Trained teachers can handle emergencies effectively. 16 In any situation, irrespective of impact and type of crisis, school teachers and relevant stakeholders act as first responders to access and notify the administration to activate emergency plans.…”
Section: Introductionmentioning
confidence: 99%
“…They have to do this task for an extended duration of time as specialists when law enforcement agencies and health professionals, for example, are not readily available. 15 Natural disasters like earthquakes and floods, 17 have a long history of property as well as human damage. Natural disasters damage schools as well as students.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation